دراسة مستويات فيتامين د في المصل عند مرضى الربو القصبي البالغين - حجازية مالك; خياط محمد عماد; صالح فاطر (Latakia University Journal -Medical Sciences Series, 2019)
خلفية : يمثّل الربو واحداً من أشيع الأمراض المزمنة و هو مشكلة صحيّة عامّة على المستوى العالمي. تلعب أجهزة المناعة البدئية و المكتسبة دوراً هاماً في الآلية الإمراضية للربو . يملك الفيتامين D تأثيرات عديدة على المناعة البدئية و المكتسبة و التي قد تكون ذات صلة بالوقاية الأولية من الربو ، الحماية من مراضة الربو. الهدف : تقييم المستوى المصلي للفيتامين D لدى مرضى الربو القصبي . المواد و الطرق : كانت هذه دراسة حالة – شاهد أجريت في مستشفى تشرين الجامعي في اللاذقية ، سوريا، خلال الفترة الممتدّة ما بين 2017 –2018 . شملت الدراسة 100 شخص تمّ تقسيمهم إلى مجموعتين , المجموعة الأولى شملت 70 مريض ربو بالغ (30 ذكر و 40 أنثى) تراوحت أعمارهم ما بين 18 – 50 سنة مع متوسط عمر 36.5 ± 8 سنة . شملت المجموعة الثانية 30 فرد طبيعي (12 ذكر و 18 أنثى) كمجموعة شاهد , تراوحت أعمارهم ما بين 20 – 53 سنة مع متوسط عمر 35.4 ± 6.5 سنة . خضع جميع الأفراد المشاركين في هذا البحث لاستجوابٍ دقيق , فحص سريري , حساب مشعر كتلة الجسم (BMI) , اختبار وظائف الرئة (spirometry) , و قياس المستوى المصلي لفيتامين D بطريقة ELISA . تم استخدام برنامج الحزمة الإحصائية للعلوم الاجتماعية (SPSS) النسخة 16 لتحليل البيانات . النتائج : أظهرت الدراسة أنّ مستوى فيتامين D لدى المرضى الربويين (21.4 ± 8.9 نانوغرام/مل) كان أخفض بفرق هام إحصائياً بالمقارنة مع مجموعة الشاهد (34.7 ± 6.3 نانوغرام/مل) . وجدت علاقة قوية بين مستوى فيتامين D و شدّة الربو . كان هناك علاقة سلبية هامة إحصائياً بين مستوى فيتامين D ومشعر كتلة الجسم , و علاقة إيجابية هامة إحصائياً بين مستوى فيتامين D و نسبة FEV1 من القيمة المتوقعة . الخلاصة : هنالك علاقة هامة بين الربو القصبي عند البالغين و مستويات الفيتامين D . حيث تكون المستويات المصلية أخفض عند مرضى الربو بالمقارنة مع الأصحاء و تكون أكثر انخفاضاً مع ازدياد شدة الربو, ارتفاع BMI , و انخفاض نسبة FEV1 من القيمة المتوقعة . Background : Asthma represents one of the most common chronic diseases and is a major public health problem worldwide. The innate and adaptive immune systems play an important role in the pathogenesis of asthma . Vitamin D has several effects on the innate and adaptive immune systems that might be relevant in the primary prevention of asthma, in the protection against or reduction of asthma morbidity. Aim : Assessment the level of serum vitamin D in patients with bronchial asthma. Materials and Methods : This was a case - control study conducted at Tishreen University Hospital , Lattakia , Syria , during the period between October 2017 – October 2018. This study included 100 subjects divided into two groups, First group included 70 adult asthmatic patients (40 females and 30 males), their ages ranged from 18 to 50 years with a mean age of (36.5 ± 8 y). The second group included 30 healthy adult (18 females and 12 males) as a control group, their ages ranged from 20 to 53 years with a mean age of (35.4 ± 6.5 y) . All subjects in this study were submitted to full medical history and clinical examination, calculation of body mass index (BMI) , spirometry and detection of serum vitamin D level by ELISA. SPSS software version 16 was used for data analysis. Results : The study showed that serum vitamin D level was significantly decreased in asthmatic patients (21.4 ± 8.9 ng/ml) as compared with the healthy control group (34.7 ± 6.3 ng/ml). A strong correlation between the serum vitamin D level and asthma severity was found . Vitamin D levels had a significant negative correlation with body mass index and a significant positive correlation with FEV1% predicted. Conclusion : There is an important association between adult bronchial asthma and vitamin D levels . Serum levels are lower in asthmatic patients compared to healthy controls . Levels of vitamin D are lower with increased asthma severity , increased BMI and decreased FEV1% predicted